2018
DOI: 10.1126/science.aan6490
|View full text |Cite
|
Sign up to set email alerts
|

A mitosis-specific and R loop–driven ATR pathway promotes faithful chromosome segregation

Abstract: The ATR kinase is crucial for DNA damage and replication stress responses. Here we describe a surprising role of ATR in mitosis. Acute inhibition or degradation of ATR in mitosis induces whole-chromosome missegregation. The effect of ATR ablation is not due to altered CDK1 activity, DNA damage responses, or unscheduled DNA synthesis, but to loss of an ATR function at centromeres. In mitosis ATR localizes to centromeres through Aurora A-regulated association with CENP-F, allowing ATR to engage RPA-coated centro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
269
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(307 citation statements)
references
References 30 publications
15
269
2
Order By: Relevance
“…In agreement, R loop-accumulating yeast cells have been shown to activate the S-phase checkpoint and to require it for survival [60] and head-on transcription-replication collisions enhanced by R loops have been recently shown to activate ATR in human cells [21]. Although R loop-driven replication fork stalling is likely the reason behind ATR activation, the displaced ssDNA of R loops in principle could also promote local ATR activation as it has been reported at centromeres in mitotic cells [61]. Together with our recent data [11], our results support that DNA-RNA hybrids not necessarily impact replication fork velocity.…”
Section: Discussionmentioning
confidence: 92%
“…In agreement, R loop-accumulating yeast cells have been shown to activate the S-phase checkpoint and to require it for survival [60] and head-on transcription-replication collisions enhanced by R loops have been recently shown to activate ATR in human cells [21]. Although R loop-driven replication fork stalling is likely the reason behind ATR activation, the displaced ssDNA of R loops in principle could also promote local ATR activation as it has been reported at centromeres in mitotic cells [61]. Together with our recent data [11], our results support that DNA-RNA hybrids not necessarily impact replication fork velocity.…”
Section: Discussionmentioning
confidence: 92%
“…9a). C-BERST uniquely captured multiple centromeric factors including CENP-F and ATR, which were recently reported to engage RPA-coated centromeric R loops 20 . GO analysis of the 460 C-BERST centromeric hits reveals strong functional associations with terms related to centromere maintenance or function 10 (Supplementary Fig.…”
mentioning
confidence: 96%
“…By contrast, the inhibition of the ATM‐related kinase ATR produced a profound prolongation of mitosis. A mitosis‐specific ATR pathway has previously been reported that is independent of DNA damage and replication and is distinct from the canonical ATR pathway operating in S phase . In that study, ATR was found to be recruited to centromeric R loops where it ensures chromosome segregation through CHEK1 signaling.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, ATR suppresses R loop-associated genomic instability in S phase and supports R loop-associated activation of mitosis through apparently distinct pathways. 22,29 It is apparent from our results with two complementing mutants that the latter function would not require the ATR-mediated phosphorylation of RAD50 at Ser635, a site that has been shown to be important for the S phase role of ATR 15 and is being used as a pharmacodynamic biomarker for ATR and ATM inhibition. 30 We cannot exclude the possibility that ATR could regulate mitotic progression through RAD50 in a way different from direct phosphorylation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation